Quick Reference Guide to Foliar Fungicides - Megan M. Dewdney (EDIS)
This revised 2-page reference guide provides quick access to foliar fungicide recommendations from the Florida Citrus Pest Management Guide. Verso provides guidelines for fungicide resistance management. Written by M. M. Dewdney and published by the UF Department of Plant Pathology, April 2011.